2018
DOI: 10.1111/gbb.12502
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐species systems analysis of evolutionary toolkits of neurogenomic response to social challenge

Abstract: Social challenges like territorial intrusions evoke behavioral responses in widely diverging species. Recent work has showed that evolutionary "toolkits"-genes and modules with lineage-specific variations but deep conservation of function-participate in the behavioral response to social challenge. Here, we develop a multispecies computational-experimental approach to characterize such a toolkit at a systems level. Brain transcriptomic responses to social challenge was probed via RNA-seq profiling in three dive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 66 publications
2
21
0
Order By: Relevance
“…The molecular toolkit hypothesis posits that a handful of neuromodulatory systems underlie social behavior across species ( 67 , 158-161 ). To date, explanations for how these systems mediate species differences in social behavior have investigated differences in receptor patterning or ligand production/release.…”
Section: Why Is It Important To Examine These System Interactions?mentioning
confidence: 99%
“…The molecular toolkit hypothesis posits that a handful of neuromodulatory systems underlie social behavior across species ( 67 , 158-161 ). To date, explanations for how these systems mediate species differences in social behavior have investigated differences in receptor patterning or ligand production/release.…”
Section: Why Is It Important To Examine These System Interactions?mentioning
confidence: 99%
“…Previous studies in social insects (ants and bees) identified expansions of gene families associated with metabolism and chemical communication functions (Simola et al 2013;McKenzie et al 2016;Wurm et al 2011;Kapheim et al 2015). Similarly, previous comparative studies across animals have emphasized genes associated with metabolism as being important in the response to social challenges (Rittschof et al 2014;Saul et al 2019), suggesting that changes in genes with metabolic functions might often be involved in social evolution across animals. Indeed, previous research indicates that social spiders may have lower metabolic rates than their solitary relatives (Zimmerman 2007), further implicating changes in metabolic-related genes to the evolution of social life in spiders.…”
Section: Extensive Gene Family Evolution In Stegodyphus Social Spidermentioning
confidence: 96%
“…Behavioral genetics in non-human animals aims to establish consilience with psychiatrically relevant human systems by studying conserved behaviors and their conserved underlying neural molecular substrates. However, despite mounting evidence of deep conservation in the complex gene systems driving behavior (Saul et al, 2019a;Sinha et al, 2020;Young et al, 2019), uncertainty about the psychiatric relevance of non-human animal systems abounds in the psychiatric genetics community (National Advisory Mental Health Council Workgroup on Genomics, 2018). These doubts likely arise from longstanding and well-characterized difficulties in replicating non-human animal behavioral findings (Crabbe et al, 1999) as well as the failure to translate psychiatric genetics results from any species into the clinic (Hyman, 2012).…”
Section: Introductionmentioning
confidence: 99%